2016
DOI: 10.1515/pjvs-2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum cytokine levels in recurrent airway obstruction

Abstract: Recurrent airway obstruction (RAO) represents a serious health problem and is traditionally classified as an allergic disease, where contact with an antigen can induce clinical airway inflammation, bronchial hyper-responsiveness and reversible airway obstruction. Previous studies have demonstrated the presence of the Th2 response in the lungs of human patients with asthma and horses with heaves. These cells are involved in the production of cytokines which regulate the synthesis of immunoglobulins. 40 horses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Researchers have tried to characterise the cytokine profile during an asthma exacerbation. However, the published results are still inconsistent, especially those regarding the expression of INF-γ, IL-4, IL-5, and IL-13 [5][6][7][8]. Although the immunological pathway of this disease has not been fully determined, the significant contribution of the T cells in the pathogenesis of the disease has been confirmed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Researchers have tried to characterise the cytokine profile during an asthma exacerbation. However, the published results are still inconsistent, especially those regarding the expression of INF-γ, IL-4, IL-5, and IL-13 [5][6][7][8]. Although the immunological pathway of this disease has not been fully determined, the significant contribution of the T cells in the pathogenesis of the disease has been confirmed.…”
Section: Introductionmentioning
confidence: 98%
“…Results regarding the predominant participation of either Th1 or Th2 remain inconsistent. It is assumed that this may be due to a mixed Th1/Th2 response or a Th1/Th2-imbalance [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical examination prior to the procedure did not reveal any abnormalities and the horse was classified as healthy. The horse was restrained in a stock and sedated with 0.01 mg/kg of detomidine (Domosedan, Orionpharma, Espoo, Finland) and 0.01 mg/kg of butorphanol (Morphasol, aniMedica, GmBH, Senden-Bösensell, Germany) [8]. A twitch was additionally used.…”
Section: Case Presentationmentioning
confidence: 99%
“…Some studies showed a statistically significant increase in the activity of antioxidant enzymes in ill horses, while other studies showed a decrease in activity of these enzymes (18,22). Inconsistent results may be associated with the exacerbation of symptoms, horse maintenance or any treatment administered (1). High activity of antioxidant enzymes in different studies and low in others suggested that redox system is upregulated during exposure to dusty straw and hay to combat oxidative stress (22,65).…”
Section: The Enzyme Triad In Raomentioning
confidence: 99%
“…This is due to the pathophysiology of the disease and its different course. RAO is a disease that occurs in middle-aged horses, consisting of inflammation and gradual bronchospasm with bronchial walls rebuilding, and excessive production of mucus (1). It occurs most commonly in horses kept in stables, exposed to dust and fed low-quality hay.…”
Section: Introductionmentioning
confidence: 99%